Non-iterative Wide-modulation-index Switching-angle Calculation Techniques for 15-level Binary Cascaded H-bridge Multilevel Inverter - J. A. Soo; M. S. Chye; Y. C. Tan; S. L. Ong; J. H. Leong; T. Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Cascaded H-bridge multilevel inverter (CHBMI) is able to generate a staircase AC output voltage with low switching losses. The switching angles applied to the CHBMI have to be calculated and arranged properly in order to minimize the total harmonic distortion (THD) of the output voltage waveform. In this paper, two non-iterative switching-angle calculation techniques applied for a 15-level binary asymmetric CHBMI are proposed. Both techniques employ a geometric approach to estimate the switching angles, and therefore, the generated equations can be solved directly without iterations, which are usually time-consuming and challenging to be implemented in real-time. Apart from this, both techniques are also able to calculate the switching angles for a wide range of modulation index. The proposed calculation techniques have been validated via MATLAB simulation and experiment.